PENGARUH MODEL DISCOVERY LEARNING MENGGUNAKAN METODE BRAINSTORMING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - YULANDARI, YULANDARI; SUKASNO, SUKASNO; ROSALINA, ELYA (Universitas Muhammadiyah Bengkulu, 2020)
This research was took based on the low ability of Mathematical Problem Solving by students. The objective at this research was there were any impact teaching Models Discovery Learning Using Brainstorming Methods toward studentsâ€™ ability in Mathematical Problem Solving at grade VIII SMP Al-Ikhlas Lubuklinggau in academic years 2019/2020. The research method used is of pure experiments. The population in this experiment is all of Students gradeÂ VIII SMP Al-Ikhlas Lubuklinggau that consist of 73 students and the sample as exsperimental class was VIII.A and as the class control was VIII.B.In collecting the data the researcher used test. The data that was collected, it was analysed by z-test .The result showed that at level of sicnificances ð›¼ = 0,05, it can be concluded that there were impact teaching Models Discovery Learning Using Brainstorming Methods toward studentsâ€™ ability in Mathematical Problem Solving at grade VIII SMP Al-Ikhlas Lubuklinggau in academic years 2019/2020. The avarage of studentsâ€™ score in Mathematical Problem Solvingability after being threated in the class experiment is 17,03 andcontrol class is 13,65Keywords : Discovery learning, Brainstorming, Mathematical problem solving